Point blank / 2. - Horowitz, Anthony, 1955- (Horowitz, Anthony, 1955- Alex Rider adventure., 2002)
Fourteen-year-old Alex continues his work as a spy for the British MI6, investigating an exclusive school for boys in the French Alps.